PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE ROTATING TRIO EXCHANGE (RTE) TERHADAP HASIL BELAJAR DAN MINAT BELAJAR MATEMATIKA SISWA KELAS V SDN PINGGIR PAPAS 1 SUMENEP - Nor Fajariyatul Hasanah; Mohammad Edy Nurtaman; Umi Hanik (Program Studi Pendidikan Guru Sekolah Dasar, 2019)
This reseach aims to determine 1) the effect of cooperative learning type Rotating Trio Exchange (RTE) on students’ learning outcomes, 2) interests, and 3) implementation of learning. This research is a quantitative research using Quasi Experiment Design with the Nonequivalent Control Group Design form, implemented in class V SDN Pinggir Papas 1 Sumenep 36 students. Based on result of hypothesis test result of student learning using t-test two independent samples obtained tcount = 2,219 ttable = 2.032 so Ho was rejected and Ha was accepted, meaning there are difference of learning result which significant between experiment class and control class. While the students’ learning interest in learning using cooperative learning type Rotating Trio Exchange (RTE) of 83.25% with high category. Teacher activity in the learning process in the experimental class has a percentage 75% with a very good category and student activity in the experimental class has a percentage 75% with a good category in the first meeting and 84,44% with a good category in the second meeting So it can be concluded that the learning of mathematics using the model of cooperative learning type Rotating Trio Exchange (RTE) influenced the result of learning, can foster interest in students learning, teacher does the learning well according to the stage of RPP, and student are active with help each other in mastering the subject matter.